In-vitro and in-silico evaluation of rue herb for SARS-CoV-2 treatment - Maliha Khandoker Minu (22224733) (2024)
SARS-CoV-2, a β-coronavirus responsible for the COVID-19 pandemic, has resulted in approximately 4.9 million fatalities worldwide. Despite the urgent need, there is currently no specific therapeutic developed for treating or preventing SARS-CoV-2 infections. The virus enters the host by engaging in a molecular interaction between the viral Spike glycoprotein (S protein) and the host ACE2 receptor, facilitating membrane fusion and initiating infection. Inhibiting this interaction could impede viral activity. Therefore, this study aimed to identify natural small molecules from perennial rue herb (Ruta graveolens) as potential inhibitors against the S protein, thus preventing virus infection. Initially, a screening process was conducted on 53 compounds identified from rue herbs, utilizing pharmacophore-based virtual screening approaches. This analysis resulted in the identification of 12 hit compounds. Four compounds, namely Amentoflavone (CID: 5281600), Agathisflavone (CID: 5281599), Vitamin P (CID: 24832108), and Daphnoretin (CID: 5281406), emerged as potential S protein inhibitors through molecular docking simulations, exhibiting binding energies in kcal/mol of −9.2, −8.8, −8.2, and −8.0, respectively. ADMET analysis revealed favorable pharmacokinetics and toxicity profiles for these compounds. The compounds’ stability with respect to the target S protein was evaluated using MD simulation and MM-GBSA approaches. The analysis revealed the stability of the selected compounds with the target protein. Also, PCA revealed distinctive movement patterns in four selected compounds, offered valuable insights into their functional behaviors and potential interactions. In-vitro assays revealed that rue herb extracts containing these compounds displayed potential inhibitory properties against the virus, with an IC50 value of 1.299 mg/mL and a cytotoxic concentration (CC50) value of 11.991 mg/mL. The compounds derived from rue herb, specifically Amentoflavone, Agathisflavone, Vitamin P, and Daphnoretin, show promise as candidates for the therapeutic intervention of SARS-CoV-2-related complications. Other Information Published in: International Immunopharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.intimp.2024.113318